Let the speed of slower ship be x kmph

So the speed of faster ship will be (x+6)kmph

Distance covered by them in 2hr will be

Slower ship=2x Faster ship=2(x+6)=2x+12 Both ships are 60km apart

Using pythagoras theorem, 60^2=(2x)^2+(2x+12)^2

3600=8x^2+48x+144

x^2+6x-432=0

x^2+24x-18x-432=0

x=18,-24 speed can not be negative so x=18

Hence the speed of the slower ship will be 18kmph.So option b is the correct answer

So the speed of faster ship will be (x+6)kmph

Distance covered by them in 2hr will be

Slower ship=2x Faster ship=2(x+6)=2x+12 Both ships are 60km apart

Using pythagoras theorem, 60^2=(2x)^2+(2x+12)^2

3600=8x^2+48x+144

x^2+6x-432=0

x^2+24x-18x-432=0

x=18,-24 speed can not be negative so x=18

Hence the speed of the slower ship will be 18kmph.So option b is the correct answer